Integração interfuncional e a gestão de projetos: Estudo de caso em uma empresa estatal - Ribeiro, Felipe Tadeu (2019)
Although there are significant differences of management models and objectives between public and private organizations, the adoption of established practices in business has become common at the state field. It includes the creation of a Project Management Office (PMO) and the adoption of best project management practices. Successful projects require the commitment of several departments within an organization. In this respect, enabling good cross-functional integration between these departments is essential for the organization to achieve its objectives. This research aims at analyzing how cross-functional integration can provide support to a project management office (PMO) in the charge of investment projects in a Brazilian mixed economy company. A case study was conducted at a large state-owned company, in January 2019. Seventeen interviews were conducted with superintendents, managers, engineers and technicians who work directly with project management within this organization. The results showed that there are five integration factors that support the operation of the PMO, generating the following impacts: Improvement of the control over the progress of the processes; Efficiency of processes / projects; and Standardization of processes. Within the processes managed by the PMO, there are eight moderating factors of integration that are elements that generate a low level of integration between the areas. Moreover, there are seven elements of controversy among the interviewees. Both the moderating factors and the elements that were the subject of controversy influence, in some way, the support that the integration factors provide for the operation of the PMO. The integration factors are linked to the collaborative construct, while the moderating factors are linked to the interaction construct, evidencing the lack of administrative actions to improve integration in project management. This work outlines new concerns about the issues under analysis and evidence the need for further research. Finally, an improvement proposal for the managers of the studied organization is presented, in order to improve the organizational performance through the management of the cross-functional integration in the processes of project management.